The production and dissemination of knowledge scientific by nurses clinicians - Dyniewicz, Ana Maria; Guariente, Maria Helena (Revista de Enfermagem UFPE on line, 2008)
ABSTRACT Objective: to report nurses’ experiences who advise groups of searches in hospitals. Method: we selected two experiences. The first between 2003 and 2006 involving clinics nurses and other health professionals, in partnership of university hospital, community health center and School of Nursing all of them private. The second in public service, between 1999 and 2002, in partnership of School of Nursing and Directors of Nursing at University Hospital. Results: in the private service were produced eleven research presented at scientific events; eight research projects completed and sent for publication; six publications in journals indexed; four conferences, two forums; two courses; four projects in progress. In public service, either alone or in partnership with teachers and students were produced 129 research projects, 151 scientific papers presented at events; 36 published papers, six scientific papers rewarded. Conclusion: the main difficulties in investigative action by clinics nurses were with the structural organization with impasses in the process of work; weaknesses of interactions at various levels professionals; difficulties with the scientific method, among others. Although not yet part of the vast majority of services of the research by nurses in hospital they activities are key to expanding knowledge, practice review, to know the scientific and social transformations, among other ways to show your creative and innovative potential theses nurses, together with their practical experiences among other benefits professional, personal and health teams. Descriptors: nursing; clinical nursing research; health services. RESUMO Objetivo: relatar experiências de enfermeiras que assessoram grupos de pesquisas em hospitais. Métodos: foram selecionadas duas experiências, a saber: a primeira, entre 2003 e 2006 envolvendo enfermeiras assistenciais e outros profissionais da área da saúde, em parceria de hospital universitário, centro de saúde comunitário e faculdade de enfermagem particulares; a segunda, em serviço público, entre 1999 e 2002, em parceria de Faculdade de Enfermagem e Diretoria de Enfermagem de hospital universitário. Resultados: no serviço particular foram produzidos 11 trabalhos apresentados em eventos científicos; oito projetos de pesquisa concluídos e encaminhados para publicação; seis publicações em periódicos indexados; quatro palestras; dois fóruns; dois cursos de extensão; quatro projetos em andamento. No serviço público, isoladamente ou em parceria com os professores e alunos foram produzidos 129 projetos de pesquisa; 151 trabalhos científicos apresentados em eventos; 36 artigos publicados; seis trabalhos científicos premiados. Conclusão: as principais dificuldades na ação investigativa por enfermeiras assistenciais foram estruturais ecoando em impasses no processo de trabalho; fragilidades de interações em diferentes níveis hierárquicos; dificuldades com o método científico, entre outras. Embora ainda não faça parte da grande maioria dos serviços, as pesquisas por enfermeiras assistenciais, são fundamentais para ampliar conhecimentos, rever práticas, acompanhar as transformações tecnológicas e sociais, entre outras possibilidades que mostrem seu potencial criativo e inovador, em conjunto com suas experiências práticas, entre outros benefícios profissionais, pessoais e de equipes de saúde. Descritores: enfermagem; pesquisa em enfermagem clínica; serviços de saúde. RESUMEN Objetivo: informar las experiencias de las enfermeras que asesoran grupos de investigación en hospitales. Método: se seleccionaron dos experiencias. La primera entre 2003 y 2006 con la participación de enfermeras y otros profesionales de la salud, en colaboración de Hospital Universitario, centro de salud y Escuela de Enfermería, todos de instituciones privadas. El segundo en el servicio público, entre 1999 y 2002, en colaboración de Escuela de Enfermería y Directores de Enfermería en el Hospital Universitario. Resultados: no servicio particular se produjeron once trabajos presentados en eventos científicos; ocho proyectos de investigación completado y enviado para su publicación; seis publicaciones en revistas indexadas; cuatro conferencias, dos foros, dos cursos; cuatro proyectos en curso. En el servicio público, ya sea solos o en colaboración con los profesores y los estudiantes se produjeron 129 proyectos de investigación, 151 trabajos científicos presentados en eventos; 36 trabajos publicados, seis trabajos científicos premiados. Conclusión: las principales dificultades de investigación en la acción de las enfermeras de hospitales fueron en la organización estructural con reflejos en el proceso de trabajo; debilidades de las interacciones a diversos niveles profesionales, las dificultades con el método científico, entre otros. Las investigaciones por enfermeras de servicios de salud son poco conocidas, mas fundamentales para ampliar los conocimientos de la práctica; conocer las transformaciones científicas y sociales, entre otras como formas de mostrar su creatividad y potencial innovador, junto con sus experiencias prácticas, entre otros beneficios profesionales, personales y de los equipos de salud. Descriptores: enfermería; investigación en enfermería clínica; servicios de salud.